PENGARUH SUHU PENGERINGAN SPRAY DRYER TERHADAP SIFAT FISIK DAN AKTIVITAS ANTIOKSIDAN TABLET EKSTRAK BUAH MAHKOTA DEWA (Phaleria macrocarpa Boerl.) - Irfanianta Arif Setyawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
Phaleria (Phaleria macrocarpa Boerl.) contains flavonoids with antioxidants to prevent free radical that can cause cancer. This study aimed to determine the effect of drying temperature in spray dryer on the physical properties and antioxidant activity of the tablet from mahkota dewa fruit extract. Extraction process was performed by percolation technique with ethanol 70%. Extracts were made into powder using a spray dryer with a variation of drying temperature. The tablets were produced by direct compression method then the physical properties of powder, tablets physical properties and antioxidant activity were tested. Based on the results, the tablet with drying temperature of 70°C produced 6.9 ± 0.52 kg hardness, 7.38 ± 0.21 minutes disintegration time and 6.80 ± 2.85 %EDA. Tablet with drying temperature of 90°C produced 7.55 ± 0.35 kg hardness, 7.37 ± 0.11 minutes disintegration time, and 3.68 ± 0.73 %EDA. Tablet with drying temperature of 110°C produced 8.33 ± 0.21 kg hardness, 8.49 ± 0.08 minutes disintegration time, and 1.84 ± 0.87 %EDA. The results of this research showed that the increasingly of spray dryer temperature effect on the higher of tablet hardness and disintegration time, also decrease the anti oxcidant activity (p < 0.05).